GENDER PATTERN IN PARTICIPATION AND PERFORMANCE AT MATHEMATICS OLYMPIADS - Meremikwu, Anne N.; Ekwueme, Cecilia O; Enukoha, Obinna I. (Advances in Social Sciences Research Journal, 2014)
Rating of schools, regions and countries in mathematics performance is often based on olympiad results. International Mathematics Olympiad (IMO) was male-dominated with < 10% contestants being females from 1959 to 2012. Study analyzed math olympiad results for 6769 female (47.1%) and 7595 male (52.9%) Nigerian students. More males (3137/7595; 41.3%) than females (2677/6769; 39.5%) had scores above average total scores (Mantel-Haenszel =4.578, OR 0.92 (95% CI: 0.86 to 0.99; p < 0.001). Scores in objective question were better for males then females (Kruskal-Wallis =16.80; p<0.0001). Females had higher scores in theory question (KW- H test=14.96, p<0.001). Gender differences in participation and performance was marginal in the Nigerian contest. Implications of findings for gender inequity in mathematics olympiads is discussed. Key words: Gender, Mathematics, Olympiad, Inequity, students